A 1‐year follow‐up study of capacity to love and work: What components of borderline personality disorder most impair interpersonal and vocational functioning?. (22nd August 2018) - Miller, Caitlin E.; Lewis, Kate L.; Huxley, Elizabeth; Townsend, Michelle L.; Grenyer, Brin F.S.
Abstract: Background: For individuals with borderline personality disorder (BPD), both the reduction in symptoms and the improvement of vocational and interpersonal function (psychosocial function) are important for recovery. Research suggests that some components of BPD make it harder to achieve functional recovery; however, findings are varied and inconclusive. The present study assesses recovery over time in BPD, investigates which symptoms make it harder to function and explores the relationships between these symptoms. Method: One hundred ninety‐nine consecutively recruited individuals in psychological treatment for personality disorder were studied over 12 months. Measures of BPD symptom severity at intake were used to predict improvements in social and vocational function at follow‐up. Exploratory modelling was conducted to understand the relationships between symptoms and function. Results: Following 12 months of treatment, symptoms and functioning improved. Those who experienced more severe emptiness, impulsivity and self‐harm had worse outcomes. A relationship between chronic emptiness at intake and impaired vocational outcome (days out of work) at follow‐up was found, mediated by severity of impulsivity and frequency of self‐harm. Conclusion: Chronic emptiness is associated with dysfunctional behaviours such as impulsivity and self‐harm, and poor psychosocial improvement. Interventions targeting chronic emptiness in those most vulnerable may improve functional outcomes. © 2018 John Wiley & Sons, Ltd.